Five brides - Everson, Eva Marie (Tyndale House Publishers, Inc., 2015)
"Five single, fiercely independent women live together in a Chicago apartment in the early 1950s but rarely see one another. One Saturday afternoon, as they are serendipitously together downtown, they spy a wedding dress in a storefront window at the famous Carson, Pirie, Scott & Co. After trying it on--much to the dismay of the salesclerk and without a single boyfriend or date between the five of them--they decide to pool their money to purchase it. Can one dress forever connect five women who live together only a short time before taking their own journeys to love and whatever comes happily ever after?"--Amazon.com.